The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/pc.27416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weaving parameter and resin structure of lightweight integrated multifunctional composite on thermal protection performance in extreme environment

Abstract: This article reports a novel lightweight integrated multifunctional composite (LIMC) with good thermal ablative and insulating properties for high temperature extreme environment. LIMC, which is an integrated woven carbon fiber preform reinforced phenolic aerogel composites, was prepared using vacuum impregnation and ambient pressure drying. The as-prepared LIMC consisted of a dense surface layer exposed to environment, and a lightweight insulation zone to manage the heat load. The influences of weaving parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The cross-section of the established parametric unit-cell model is shown in Figure 2B, where the geometric parameters of the unit-cell are calculated using Equations (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Statistical Analysis Of Yarnsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-section of the established parametric unit-cell model is shown in Figure 2B, where the geometric parameters of the unit-cell are calculated using Equations (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Statistical Analysis Of Yarnsmentioning
confidence: 99%
“…[1][2][3][4][5] Recently, carbon fiber/phenolic laminated composites are an important candidate material for TPS. [6][7][8] However, one of the key challenges is that limited by the interfacial delamination, which especially results in the ablation spalling and influences the final strength. [9][10][11] At present, 2.5D woven structure is recognized as an effective method to meet the extreme environment.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Numerous researchers have demonstrated that the physical compounding of carbon fiber fabric (CF) and PRAs matrix strengthens the mechanical and ablation resistance properties of the composites. [22][23][24][25] Therefore, the development of synergistic reinforced composites based on ceramizable PRA matrixes is expected to achieve good ablation resistance and thermal insulation at high-temperature extremes.…”
mentioning
confidence: 99%